Mối quan hệ động giữa giá vàng, chỉ số thị trường chứng khoán và tỷ giá ở Việt Nam: Tiếp cận bằng phương pháp Canonical - Vine Copula - Trần Ngọc, Tuấn; Vũ Việt, Quảng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
In this paper, the authors aim to investigate the dynamic relationship among the gold price, VN-Index and VND/USD exchange rate in Vietnam. To investigate this relationship, the dependence modeling using Vine Copula (specifically Canonical - Vine Copula, or Cvine Copula) has been utilized, which is supposed to provide better flexibility, allowed the modeling of complex dependency patterns for high-dimensional distributions, compared to traditional approaches. Using the sample of weekly rate of return on gold price, VN-Index, and USD/VND exchange rate in Vietnam, over 10 years from January 8, 2007 to March 19, 2018, this study has documented that VND/USD exchange rate is strongly related to domestic gold price and VN-Index. Empirical evidence also shows that when the market is operating normally or stably, the relationship between exchange rate and gold price, as well as VN-Index and gold price, with and without VND/USD exchange rate condition, are not significant. However, the relationship between exchange rate and VN-Index is strong, in which, an increase in VND/USD exchange rate (a depreciation in VND) leads to a drop in VN-Index. The empirical results of sub-periods show that the dependency structure and dependency level of the asset pairs change in most of the time periods considered.